EVALUASI PENYIMPANAN VAKSIN COVID-19 DI RUMAH SAKIT DAERAH MADANI KOTA PEKANBARU: EVALUASI PENYIMPANAN VAKSIN COVID-19 DI RUMAH SAKIT DAERAH MADANI KOTA PEKANBARU - seftika sari; Tiwi Fradilah (Lembaga Penelitian Sekolah Tinggi Ilmu Farmasi Jl. Kamboja Simpang Baru-Panam, Pekanbaru, Riau 28293 Telp. (0761) 588006, Fax. (0761) 588007 e-mail: editor-jpfi@stifar-riau.ac.id, 2022)
Vaccines are biological products that are very fragile and easily damaged, so they require special handling in their management. RSD Madani is responsible for vaccine storage. Vaccine storage is a way to maintain the condition of the vaccine not being damaged so that the vaccine remains in good condition, thereby ensuring the quality of the vaccine. The purpose of this study was to evaluate the storage of the COVID-19 vaccine at the Regional Madani Hospital in Pekanbaru City against the 2020 CDOB standard and the storage indicators for the covid-19 vaccine SK of the Director General of Disease Prevention and Control Number HK.02.02/4/1/2021. The sample in this study was the storage room for the COVID-19 vaccine and all storage data for COVID-19 vaccine preparations in the Pharmacy Installation Warehouse at the Madani Regional Hospital, Pekanbaru City. This study uses a descriptive method, where the data collection method is by observing and interviewing the person in charge of the COVID-19 vaccine storage warehouse. The results showed that the storage of the Covid-19 vaccine at the Madani regional hospital in Pekanbaru city as a whole was not in accordance with the appropriate indicator regulations, namely, 33.33% for officers and training, 75% for buildings, 50 for building facilities. %, 84.6% for storage operations, 30.76% for storage maintenance, and 33.33% for qualification, calibration and validation.